CMOS X-ray imager for dental radiography - Ramos, N. F. (2003)
This paper describes a 64 pixels X-ray imager architecture and fabrication process. The imager is composed by a 8×8 photodiodes array, fabricated in CMOS process, and an array of wells £lled with scintillating crystals. A thick-£lm of aluminum is etched in order to achieve square wells with 500 um depth. The wells are filled with CsI:Tl scintillating crystals and placed above the photodiodes. The scintillating crystals convert the X-ray energy into visible light, which is guided into the photodiodes by the re¤ective aluminum walls, avoiding crosstalk between adjacent detectors. Usually, the spatial resolution of the scintillating x-rays detectors is identical to the scintillators thickness. By using the light guides, the scintillator thickness can be adjusted in order to achieve optimal absorption ef£ciency, since the spatial resolution is established by the pixel size (200 um side).